Assessment of assisted natural regeneration (ANR) implementation in Carood Watershed, Bohol, Philippines - Simacon, Angeline U.
This study evaluated Assisted Natural Regeneration (ANR) implementation in Carood Watershed, Bohol, Philippines, using a mixed-methods approach across three municipalities Anda, Candijay, and Guindulman Analysis of variance revealed significant differences between ANR and non-ANR sites ANR sites exhibited substantially higher biodiversity metrics, species count (mean 63.3), Shannon-Wiener diversity index (mean = 3.66), and Margalef richness index (mean 10.08) compared to Baseline (19, 2.71, 4.37) and Control sites (38, 324, 6.48). These differences were statistically significant (p<0.05) with F-ratios of 14.8, 11.25, and 14.98 respectively Importantly, Pielou's evenness index remained consistent across all sites (0.88-0.90), with a non-significant F-ratio (0.95, p>0.05), indicating that species distribution patterns were maintained despite increased diversity. Vegetation assessments classified ANR sites as having "very high" diversity with native species dominance. Rhus kattensix (45 trees in Katipunan) and Ardisia elliptica (35 trees in Tawid) were prevalent. Above-ground biomass accumulation was substantial in ANR sites, with R. taltensis (3,261.20 kg) and Elaeocarpus macranthus (2,032.37 kg) as major contributors. Conservation-significant species including vulnerable Macaranga grandifolia and endangered Vitex parviflora were documented in ANR sites, contrasting with baseline sites dominated by fewer species like Antidesma ghaesembilla. Soil quality improved significantly in ANR sites, with increased organic carbon (4.19-5.11% vs. 3.38% in baseline), more favorable pH levels (6.30-6.40 vs. 4.86), and enhanced nutrient availability, particularly phosphorus (up to 62.86 mg/kg vs. 3.04 mg/kg). The results provide strong evidence for ANR's ecological effectiveness, demonstrating its capacity to enhance forest biodiversity while maintaining natural species distribution patterns. Stakeholder interviews revealed positive community perceptions and strong technical knowledge of ANR. Economic considerations emerged as significant motivators for community participation, highlighting the socioeconomic dimension of forest restoration. These findings align with previous research by Shono et al. (2007) and Chazdon and Guariguata (2016), confirming ANR as an approach that simultaneously promotes biodiversity conservation, enhances ecosystem services, and engages communities through economic incentives and collaborative governance. Recommendations include strengthening institutional frameworks, developing site-specific protocols, enhancing community engagement, and conducting further research to optimize implementation. The study supports upscaling ANR in national forest restoration initiatives, contributing to the Philippines' Paris Agreement commitments.